Radical Scavenging Is Not Involved in Thymoquinone-Induced Cell Protection in Neural Oxidative Stress Models - Christopher Krewenka; Sandra Rizzi; Chi Huu Nguyen; Marcin Delijewski; Lars Gille; Katrin Staniek; Johanna Catharina Duvigneau; Khaled Radad; Andrea Müllebner; Barbara Kranner; Rudolf Moldzio (MDPI AG, 2023)
Thymoquinone (TQ), an active compound from Nigella sativa seeds, is often described as a pharmacologically relevant compound with antioxidative properties, while the synthesis of TQ in the plant via oxidations makes it inapplicable for scavenging radicals. Therefore, the present study was designed to reassess the radical scavenging properties of TQ and explore a potential mode of action. The effects of TQ were studied in models with mitochondrial impairment and oxidative stress induced by rotenone in N18TG2 neuroblastoma cells and rotenone/MPP+ in primary mesencephalic cells. Tyrosine hydroxylase staining revealed that TQ significantly protected dopaminergic neurons and preserved their morphology under oxidative stress conditions. Quantification of the formation of superoxide radicals via electron paramagnetic resonance showed an initial increase in the level of superoxide radicals in the cell by TQ. Measurements in both cell culture systems revealed that the mitochondrial membrane potential was tendentially lowered, while ATP production was mostly unaffected. Additionally, the total ROS levels were unaltered. In mesencephalic cell culture under oxidative stress conditions, caspase-3 activity was decreased when TQ was administered. On the contrary, TQ itself tremendously increased the caspase-3 activity in the neuroblastoma cell line. Evaluation of the glutathione level revealed an increased level of total glutathione in both cell culture systems. Therefore, the enhanced resistance against oxidative stress in primary cell culture might be a consequence of a lowered caspase-3 activity combined with an increased pool of reduced glutathione. The described anti-cancer ability of TQ might be a result of the pro-apoptotic condition in neuroblastoma cells. Our study provides evidence that TQ has no direct scavenging effect on superoxide radicals.